ATTITUDES TO MUSIC THERAPY AS A METHOD OF MAINTAINING PSYCHICAL HEALTH OF PEOPLE SUFFERING FROM PSYCHIATRIC DISORDERS - Straksiene, Diana; Radzeviciene, Liuda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article presents the pilot research on the attitudes to music therapy of people who have psychiatric diseases. The attitudes were analyzed according to the preferred form of relax and leisure; information they have about the impact of music therapy on psychical health of individuals, expedience of music therapy for maintaining positive psychical health, the attitude to music therapy as a tool of personal empowerment and the preferred type of music of the respondents, the level of their music education, the type of music they used for relax activities, the meaning of music as a tool of therapy. It was revealed that music therapy is acceptable for the most of the respondents, nevertheless, there is lack of information for patients and applied activities of music therapy in the processes of treatment or rehabilitation.